Municipal officials’ subjective distress in coordinating with the national government during the decontamination project of radioactive materials in Fukushima: A qualitative study - Tomoo Hidaka; Takeyasu Kakamu; Hideaki Kasuga; Yuko Suzuki; Toshihiro Terui; Shizuka Kawamoto; Tatsuya Sato (PLoS ONE, 2026)
Municipal government officials (MGOs) have played key roles in managing decontamination project of radioactive materials in the aftermath of the Fukushima Daiichi Nuclear Power Plant (FDNPP) accident. However, the subjective distress experienced by MGOs during the decontamination project, mainly stemming from challenges in coordination with the national government, is not yet fully documented. The purpose of this study is to descriptively understand the nature and causes of subjective distress among MGOs and to make an exploratory conceptual model of the process through which such subjective distress becomes manifest. Narratives from three MGOs were collected through interviews and subjected to qualitative analysis using the Steps for Coding and Theorisation method. For the first purpose, the results indicate that inconsistencies in national reconstruction and decontamination designs impose substantial burdens at the operational level; these burdens are further amplified by inadequate management by national authorities, and subjective distress emerges through a breakdown of trust among national government officials, municipalities, and residents. For the second purpose, an exploratory conceptual model explaining the progression toward subjective distress through the following four stages was created: the emergence of distrust and adversarial orientations toward the national government, the dilemma of occupying an intermediate position, the erosion of ties with residents, and the threat to professional pride. Overall, through experiences such as questioning the national government’s reconstruction policies, enduring the psychological burden of occupying an intermediate position, and witnessing a breakdown in trust with residents, MGOs may find their professional pride undermined; consequently, subjective distress, manifesting as a profound sense of emptiness, may arise. As MGOs are likely to stand at the frontline of managing post-radiation-disaster reconstruction and decontamination efforts, it is essential to develop protective measures for their mental health from both macro-level, organisational perspectives and micro-level, occupational and psychological perspectives.